Women’s Empowerment In Village Budget From A Gender Perspective: A Case Study in Gampong Jambo Papeun, South Aceh - Annisah Putri; Ardiansyah Ardiansyah; Ibnu Phonna Nurdin; Iqbal Ahmady; Rizfa Maghfirah; Wardatul Jannah (Indonesian Scientific Journal, 2025)
This community service program explores women’s empowerment in village budgeting from a gender perspective in Gampong Jambo Papeun, South Aceh. Women’s participation in budget planning remains limited due to cultural norms, lack of awareness, and restricted access to decision-making forums. Employing a participatory approach, the program incorporated surveys, interviews, interactive workshops, and deliberation simulations to enhance women’s budget literacy and advocacy skills. These activities encouraged women to identify and articulate needs often overlooked in village planning, such as health, skills training, and economic empowerment. Mentoring and simplified educational materials helped maintain their engagement. The findings suggest that gender-responsive budgeting (GRB) can enhance inclusivity while striking a balance between physical infrastructure and social development priorities. Although the initiative successfully raised awareness and participation, challenges such as low attendance and its focus on a single village limit its broader applicability. Nevertheless, this case offers a practical model for promoting women’s involvement in rural budgeting processes, contributing to more equitable and sustainable local development.